Cellulose nanocomposites with nanofibres isolated from pineapple leaf fibers for medical applications - Cherian, Bibin Mathew [UNESP]; Leão, Alcides Lopes [UNESP]; de Souza, Sivoney Ferreira; Manzine Costa, Ligia Maria; de Olyveira, Gabriel Molina; Kottaisamy, M.; Nagarajan, E. R.; Thomas, Sabu (Elsevier B.V., 2011)
Nanocellulose is the crystalline domains obtained from renewable cellulosic sources, used to increase mechanical properties and biodegrability in polymer composites. This work has been to study how high pressure defibrillation and chemical purification affect the PALF fibre morphology from micro to nanoscale. Microscopy techniques and X-ray diffraction were used to study the structure and properties of the prepared nanofibers and composites. Microscopy studies showed that the used individualization processes lead to a unique morphology of interconnected web-like structure of PALF fibers. The produced nanofibers were bundles of cellulose fibers of widths ranging between 5 and 15 nm and estimated lengths of several micrometers. Percentage yield and aspect ratio of the nanofiber obtained by this technique is found to be very high in comparison with other conventional methods. The nanocomposites were prepared by means of compression moulding, by stacking the nanocellulose fibre mats between polyurethane films. The results showed that the nanofibrils reinforced the polyurethane efficiently. The addition of 5 wt% of cellulose nanofibrils to PU increased the strength nearly 300% and the stiffness by 2600%. The developed composites were utilized to fabricate various versatile medical implants. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Pineapple leaf fibre (PALF); Cellulose Nanofibres; Polyurethane; Nanocomposites; Medical application